Improving decision making in acute healthcare through implementation of an intensive care unit (ICU) intervention in Australia: a multimethod study. Issue 3 (9th March 2019) - Clay-Williams, Robyn; Blakely, Brette; Lane, Paul; Senthuran, Siva; Johnson, Andrew
Abstract : Objective: To evaluate the implementation of an intensive care unit (ICU) intervention designed to establish rules for making ICU decisions about postsurgery beds. Design: Preintervention/postintervention case study using a multimethod approach, involving two phases of staff interviews, process mapping and collection of administrative data. Setting: ICU in a 700-bed regional tertiary care hospital in Australia. Participants: 31 interview participants. Phases 1 and 2 participants drawn from three groups of staff: bedside nursing staff in the ICU, ICU specialist doctors and senior management staff involved in oversight of ICU operations. Phase 2 included an additional participant group: staff from surgery and emergency departments. Intervention: Implementation of an ICU escalation plan and introduction of a multidisciplinary morning meeting to determine ICU bed status in accordance with the plan. Main outcome measures: Interview data consisted of preintervention staff perceptions of ICU workplace cohesiveness with bed pressure, and postintervention staff perceptions of the escalation plan and ICU performance. Administrative data consisted of bed status (red, amber or green), monthly number of planned elective surgeries requiring an ICU bed and monthly number of elective surgeries cancelled due to unavailability of ICU beds. Results: Improved internal communication, decision making and cohesion within the ICU and better coordination between ICU and other hospital departments. Significant reduction in elective surgeries cancelled due to unavailability of ICU beds, χ 2 1 =24.9, p<0.0001. Conclusions: By establishing rules for decision making around ICU bed allocation, the intervention improved internal professional relationships within the ICU as well as between the ICU and external departments and reduced the number of elective surgeries cancelled.